Language preservation: The role of infographics - Ọladeji, Taiwo Mosunmọla; Adelana, Owolabi Paul; Atolagbe, Oluwaseun Dorcas (Journal of ICT in Education, 2023)
Preserving indigenous languages, notably the Yoruba language, is imperative for both cultural heritage conservation and academic advancement, particularly within linguistic studies. As one of Nigeria's top three spoken languages, the Yoruba language faces a threat to its counting and numbering systems due to English language influence, prompting a critical need for empirical investigation. To address this research gap, our quantitative study experimentally explores the impact of infographics on language instruction among seventy-one junior secondary students. Results reveal substantial gaps in students' prior exposure to infographics. Also, positive attitudes and increased engagement with infographics significantly improve comprehension of the Yoruba counting and numbering system, with no significant difference in learning outcomes based on gender. These findings underscore the potential of infographics in preserving the Yoruba language, advocating for its integration into indigenous language studies to enhance language preservation efforts. This study emphasizes the instrumental role of infographics in safeguarding cultural and linguistic heritage, advocating for their incorporation into educational strategies for indigenous languages.